Bacterial sheath brown rot of rice caused by Pseudomonas fuscovaginae in Latin America - Zeigler, Robert S.; Álvarez, E. (Scientific Societies, 1987)
Many types of symptoms associated with discolored grain have been observed on rice (Oryza sativa) sheaths, leaves, and grain in Mexico, Guatemala, Panama, Surinam, Colombia, Peru, and Brazil. These include brown necrotic lesions ranging from small specks to large brown to maroon sheath blotches. Symptoms were also expressed as a brown stripe on the sheath that could extend along the midrib of the leaf lamina for nearly its entire length. Panicles failed to emerge properly from the boot when the flag leaf sheath was severely affected, producing discolored and poorly filled grain. Grain from panicles of badly affected plants showed variable severity of symptom expression. A fluorescent pseudomonad was consistently isolated from affected tissue collected in Colombia and Surinam and reproduced symptoms upon inoculation. The pathogen was identified as Pseudomonas fuscovaginae, the causal agent of bacterial sheath brown rot of rice first described in Japan. Comparison of the physiological characteristics of isolates from Latin America, Asia, and Africa, P. fuscovaginae, and P. marginalis suggests that the designation of P. fuscovaginae as a separate species may not be appropriate. The bacterium was seed-transmitted, with seedlings showing symptoms on sheaths and leaves after 10–20 days. Heat treatment at 65 C for 6 days eradicated the pathogen from infected seed. The possibility that this pathogen is a principal causal agent of the dirty panicle disease (grain spotting, manchado de grano) is discussed.